The role of anthropometry, physical, psychological and personality for elite athletes in competitive sports - Guntoro, T. S.; Suturo; Putra, M. F. P.; Kurdi; Németh, Z.; Setiawan, E. (Pedagogy of Physical Culture and Sports, 2023)
Background and Study Aim This study aims to describe and explore the anthropometric, physical, psychological, and personality traits of elite Papuan Indonesian athletes in seven different sports, namely weightlifting, rowing, cricket, futsal gateball, sailing, and hang-gliding.